Development and validation of a new measurement instrument to assess internship experience of medical doctors in low-income and middle-income countries - Zhao, Y; Jalloh, S; Lam, PK; Kwarshak, YK; Mbuthia, D; Misago, N; Namedre, M; Phương, NTB; Qaloewa, S; Summers, R; Tang, K; Tweheyo, R; et al. (BMJ Publishing Group, 2023)
Routine surveys are used to understand the training quality and experiences of junior doctors but there are lack of tools designed to evaluate the training experiences of interns in low-income and middle-income countries (LMICs) where working conditions and resource constraints are challenging. We describe our process developing and validating a 'medical internship experience scale' to address this gap, work involving nine LMICs that varied in geographical locations, income-level and internship training models. We used a scoping review of existing tools, content validity discussions with target populations and an expert panel, back-and-forth translations into four language versions and cognitive interviews to develop and test the tool. Using data collected from 1646 interns and junior medical doctors, we assessed factor structure and assessed its reliability and validity. Fifty items about experiences of medical internship were retained from an initial pool of 102 items. These 50 items represent 6 major factors (constructs): (1) clinical learning and supervision, (2) patient safety, (3) job satisfaction, (4) stress and burnout, (5) mental well-being, and (6) fairness and discrimination. We reflect on the process of multicountry scale development and highlight some considerations for others who may use our scale, using preliminary analyses of the 1646 responses to illustrate that the tool may produce useful data to identify priorities for action. We suggest this tool could enable LMICs to assess key metrics regarding intern straining and initial work experiences and possibly allow comparison across countries and over time, to inform better internship planning and management.